Feeding non-preference by Spodoptera frugiperda and Spodoptera eridania on tomato genotypes - Bruno Henrique Sardinha de Souza; Daline Benites Bottega; Anderson Gonçalves da Silva; Arlindo Leal Boiça Júnior (Revista Ceres, 2013)
Larvae of the genus Spodoptera spp. are highly polyphagous and can cause economical losses in several agricultural crops. Given their growing importance in the tomato crop, especially for industry, this work aimed to evaluate the feeding non-preference by larvae of Spodoptera frugiperda (J. E. Smith, 1797) and Spodoptera eridania (Cramer, 1782) on tomato genotypes and classify them by the levels of resistance. The commercial cultivar Santa Clara was set as the susceptible standard and line PI 134417 as the resistant standard to evaluate the lines PI 134418, PI 126931, LA 462 and LA 716. Feeding non-preference tests were performed under non-choice and free-choice conditions to evaluate the genotype attractiveness to larvae at predetermined times after their release, as well as the leaf area consumed. Overall, the genotypes LA 716 and PI 126931 were the least attractive to S. frugiperda, whereas Santa Clara was the most attractive and consumed. For S. eridania, the genotypes PI 126931, LA 462, LA 716 and PI 134418 were the least preferred for feeding, and Santa Clara and PI 134417 were the most attractive and consumed. The genotypes LA 716 and PI 126931 are moderately resistant to S. frugiperda and S. eridania; PI 134418 and LA 462 are moderately resistant to S. eridania; PI 134417 is susceptible to S. frugiperda and S. eridania; and Santa Clara is highly susceptible to both S. frugiperda and S. eridania.